PERKEMBANGAN BAHASA PADA ANAK - Muzaiyanah Muzaiyanah (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2013)
In communication the language is an essential tool for every human being. Speaking through a person or a child will be able to develop associate (social skills) with others. Language development in children seen from language acquisition is divided into: the development of pragmatic, semantic, syntactic, morphological and phonological development. There are three factors that affect children in the language of biology, cognitive and environmental.